Democracy defence act: law and history in the parliamentary debates of the transition (1983-1984) - Velázquez Ramírez, Adrián (Universidad Nacional del Litoral, 2021)
The article discusses parliamentary debates on the «law on the protection of constitutional order and democratic life» (Law 23077), adopted on 9 August 1984 during the government of Raúl Alfonsín (1983-1989). The aim is to investigate the senses and representations that served as a justification framework, as well as in the legal rhetoric used to turn democracy into a protected legal good. In this way, the article seeks to offer a glimpse into the changes in legal discourse during the transition to democracy. On the basis of what we have called as a 'legislator's phenomenology', it is particularly relevant how the relationship between the proposed law and historical experience is established in parliamentary debates